2021
DOI: 10.1186/s13052-021-01014-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time ultrasound for tip location of umbilical venous catheter in neonates: a pre/post intervention study

Abstract: Background Recent guidelines advocate the use of real-time ultrasound to locate umbilical venous catheter tip. So far, training programs are not well established. Methods A pre/post interventional study was carried out in our tertiary neonatal intensive care unit centre to evaluate the efficacy of a training protocol in the use of real-time ultrasound. Primary outcome was the percentage in the use of real-time ultrasound. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…A recent pre/post-intervention study by Rubortone et al confirmed a reduction in the number of X-rays requested for UVC position confirmation in the postintervention phase when US was used (92.3% vs. 32.1%; p < 0.0001). However, a potential bias was the choice of the confirmatory method (X-ray or US) which was left to the attending neonatologist and was not standardised [22]. Our findings confirm these trends, in a bigger sample size.…”
Section: Goodsupporting
confidence: 80%
“…A recent pre/post-intervention study by Rubortone et al confirmed a reduction in the number of X-rays requested for UVC position confirmation in the postintervention phase when US was used (92.3% vs. 32.1%; p < 0.0001). However, a potential bias was the choice of the confirmatory method (X-ray or US) which was left to the attending neonatologist and was not standardised [22]. Our findings confirm these trends, in a bigger sample size.…”
Section: Goodsupporting
confidence: 80%
“…A recent pre/post intervention study demonstrated the feasibility of targeted training on the use of POCUS for UVC placement in NICU among neonatal medical staff. The technique was easily teachable, increased the number of UVCs correctly positioned, and reduced the number of line manipulations and chest X-rays ( 48 ).…”
Section: Insertion Of the Uvc Including New Technologiesmentioning
confidence: 99%
“…The inward migration was explained by cord stump contraction over time together with an increase in lung volume (due to the increase in the functional residual capacity, e.g., following surfactant administration), the outward migration instead was likely to result from gradual distension of the abdomen as the bowel filled with gas ( 58 ). About half the infants included in the studies experienced migration, mainly inward within 24–48 h from the catheter insertion ( 48 , 59 , 60 ).…”
Section: Migrationmentioning
confidence: 99%
“…POCUS can also be used to confirm catheter tip location in venous vascular cannulation. Ultrasound confirmed catheter tip location has been deemed to be safe and effective in midline catheters in adults, umbilical venous catheter and PICC lines in neonates, and to have good agreement with chest x-ray in central venous catheters in pediatric patients (26)(27)(28)(29).…”
Section: Vascular Cannulationmentioning
confidence: 94%